Associations of Children's Independant Mobility and Active Travel with Physical Activity, Sedentary Behaviour and Weight Status: A Systematic Review - Schoeppe, S.; Duncan, M.; Badland, H.; Oliver, M.; Curtis, Carey (Elsevier, 2013)
Objectives: This review synthesized the evidence for associations of independent mobility and active travel to various destinations with physical activity, sedentary behaviour and weight status. Design: Systematic review. Methods: A systematic search in six databases (PubMed, Scopus, CINAHL, SportDiscus, PsychInfo, TRIS) for papers published between January 1990 and March 2012 was undertaken, focussing on children aged 3–18 years. Study inclusion and methodological quality were independently assessed by two reviewers.Results: 52 studies were included. Most studies focussed solely on active travel to and/or from school, and showed significant positive associations with physical activity. The same relationship was detected for active travel to leisure-related places and independent mobility with physical activity. An inverse relationship between active travel to school and weight status was evident but findings were inconsistent. Few studies examined correlations between active travel to school and self-reported screen-time or objectively measured sedentary behaviour, and findings were unclear. Conclusions: Studies on independent mobility suggested that children who have the freedom to play outdoors and travel actively without adult supervision accumulate more physical activity than those who do not. Further investigation of children's active travel to leisure-related destinations, measurement of diverse sedentary behaviour beyond simply screen-based activities, and consistent thresholds for objectively measured sedentary behaviour in children will clarify the inconsistent evidence base on associations of active travel with sedentary behaviour and weight status.